2020
DOI: 10.1038/s41598-020-65275-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Involvement of Vernalization-related Genes in the Regulation of Cold-induced Ripening in ‘D’Anjou’ and ‘Bartlett’ Pear Fruit

Abstract: Physiological studies have characterized the conditioning requirements for a range of European pear cultivars under defined conditioning temperatures, exogenous ethylene application regimes, and other pre-harvest treatments 8-11. While exogenous ethylene treatment reduces cold conditioning needs, in most European pear cultivars it does not entirely supplant the need for cold conditioning. This indicates that cold-dependent mechanisms are partly responsible for regulating the development of ripening competency,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…Recent independent studies, as well as reviews, have indicated that such modifications to the classical climacteric ripening implicate several pathways that operate concomitantly with ethylene biosynthesis and perception, including AOX respiration, signaling by reactive oxygen species (ROS), and pathways that may be triggered by changes in epigenetic signatures (Perotti et al, 2014;Kumar et al, 2016;Farinati et al, 2017;Bucher et al, 2018;Hendrickson et al, 2019;Hewitt et al, 2020b). New advances in genome editing have provided further insight regarding potential sites for variation in ripening, as manipulation of upstream transcriptional regulators (Ito et al, 2017) leads to alterations in fruit texture, photoperiodic response, and posttranscriptional regulation of ripening-related genetic elements (Martín-Pizarro and Posé, 2018).…”
Section: Reexamining the Classical Model For Ethylene-dependent Ripeningmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent independent studies, as well as reviews, have indicated that such modifications to the classical climacteric ripening implicate several pathways that operate concomitantly with ethylene biosynthesis and perception, including AOX respiration, signaling by reactive oxygen species (ROS), and pathways that may be triggered by changes in epigenetic signatures (Perotti et al, 2014;Kumar et al, 2016;Farinati et al, 2017;Bucher et al, 2018;Hendrickson et al, 2019;Hewitt et al, 2020b). New advances in genome editing have provided further insight regarding potential sites for variation in ripening, as manipulation of upstream transcriptional regulators (Ito et al, 2017) leads to alterations in fruit texture, photoperiodic response, and posttranscriptional regulation of ripening-related genetic elements (Martín-Pizarro and Posé, 2018).…”
Section: Reexamining the Classical Model For Ethylene-dependent Ripeningmentioning
confidence: 99%
“…In zucchini and sweet pepper, cold-induced activation of AOX results in the mitigation of chilling injury (Aghdam, 2013;Hu et al, 2014;Carvajal et al, 2015). Recently, it was demonstrated that completion of cold conditioning, facilitating the S1-S2 transition, in European pear coincides with preclimacteric maxima in AOX transcript accumulation (Hendrickson et al, 2019;Dhingra et al, 2020;Hewitt et al, 2020b).…”
Section: Activation Of Aox During Ripeningmentioning
confidence: 99%
See 3 more Smart Citations